Topical treatments for Kaposi sarcoma: A systematic review. Issue 2 (8th April 2022) - Htet, Kyaw Zin; Waul, Michael Andrew; Leslie, Kieron Seymour
Abstract: Background: While treatment options exist for solitary or disseminated Kaposi sarcoma (KS) disease, there are currently no standardized clinical treatment guidelines for cutaneous KS. Objective: This systematic review seeks to identify safe and effective topical treatments for cutaneous KS lesions. Methods: We conducted a systematic review using peer‐reviewed articles from January 1970 to September 2021 published in the PubMed/MEDLINE and EMBASE databases. Results: From the initial search that yielded 590 studies, 34 met the inclusion criteria and were selected. Of the 34 studies, seven were clinical trials, 26 were case reports/series and one was a multicentre study. A total of 634 patients were included in our review. The three most common topical treatments used for cutaneous KS were imiquimod, alitretinoin and timolol. Topical alitretinoin was used in three case reports and three clinical trials. Topical imiquimod was used in eight case reports, one prospective phase II cohort study and one comparative single‐blinded non‐controlled clinical study. Topical timolol was used in nine case reports/series. Our review also identified reports of less widely used topical treatments for cutaneous KS. These include topical diphencyprone (DPCP), all‐ trans ‐retinoic‐acid, rapamycin and bleomycin‐dimethylsulfoxide (BLM‐DMSO) which achieved variable response rates but have not been widely studied. Conclusion: Topical alitretinoin, imiquimod and timolol demonstrated positive responses for cutaneous KS and the treatments were well tolerated. These three topical treatment modalities could be considered by clinicians when treating cutaneous KS. Abstract :